The evaluation of the fertilizing and yield potential of straw and cellulose manure = Ocena przydatności nawozowej obornika słomiastego i celulozowego - Słobodzian-Ksenicz, Oryna; Bojarski, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objective of the study was to determine the physicochemical properties as well as the fertilizing and crop-yielding value of straw and cellulose manure after a 6-month storage period.
Keywords: manure; straw; cellulose; yield; fertilizing value; yield potential; obornik; słoma; celuloza; plon; przydatność nawozowa